Integrasi Nilai Ikhlas dan Profesionalisme dalam Manajemen Sumber Daya Manusia di Pondok Pesantren - Mika Edison (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study examines the integration of sincerity (ikhlas) values and professionalism in human resource management (HRM) at modern Indonesian Islamic boarding schools (pesantren). Through a literature review approach enriched with social media content analysis (Instagram and TikTok Analytics), this study aims to: (1) describe the concept of ikhlas based on classical Islamic literature and contemporary kyai perspectives; (2) analyze the application of professionalism in modern pesantren HRM; and (3) formulate an integration model named PRIMA (Purposeful Sincerity, Rigorous Competence, Integrated Accountability, Mindful Leadership, Adaptive Welfare). Findings reveal that the perceived dichotomy between ikhlas and professionalism can be reconciled within a holistic and contextual HRM framework. The novelty lies in the PRIMA model as a new conceptual framework bridging Islamic epistemology and modern management principles, while leveraging social media analytics as a mirror of public perception on pesantren transformation. Practical implications include HRM policy recommendations for pesantren transitioning toward professional Islamic educational institutions.